«El cuento de nunca acabar». On José Ortega y Gasset’s Narrative Philosophy - Trotta, Francesco Giuseppe (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper delves into Ortega y Gasset’s conception of «narrative reason» within the broader context of 19th and 20th-century «narrative philosophies» (such as those put forward by Schelling or Rosenzweig). By scrutinising the boundaries that both divide and unite philosophy and narrative, the study charts the evolution of Ortega’s «narrative reason», ranging from the issue of the «essayism» in Meditations on Quixote (1914) to the concepts emerging in the 1940s and 1950s. In this endeavour, it aims to reconstruct the interaction among philosophy, myth, storytelling, and novel in Ortega’s thought, while also illustrating the pivotal role played by «narrative reason» in his critique of the metaphysical tradition, drawing comparisons with Franz Rosenzweig’s narrative philosophy. Through this comparison, the paper elucidates Ortega’s endeavour to forge a new mode of thought, rooted not in static notions of being, substance, and nouns, but in the dynamic processes of becoming and verbs. In light of this «new idea of Thinking», the paper further explores the intricate relationship between metaphor and concept, as well as the interplay between logos and mythos in Ortega’s philosophical outlook. Ultimately, «narrative reason» emerges as his perhaps most original, yet inconclusive, attempt to focus the various lines of his philosophical reflection around the central problem: that of life.
Keywords: Ortega y Gasset; narrative reason; myth; Schelling; Rosenzweig